2020
DOI: 10.12788/jhm.3535
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Guideline-Adherent Pulse Oximetry Use in Bronchiolitis

Abstract: METHODS: This multicenter qualitative study took place in the context of the Eliminating Monitor Overuse (EMO) SpO2 study, a cross-sectional study to establish rates of cSpO2 in bronchiolitis. We conducted semistructured interviews, informed by the Consolidated Framework for Implementation Research, with a purposive sample of stakeholders at sites with high and low cSpO2 use rates to identify barriers and facilitators to addressing cSpO2 overuse. Interviews were audio recorded and transcribed. Analyses were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Wolk and colleagues conducted a multicentre qualitative study of clinicians at United States hospitals with low and high continuous pulse oximetry use in bronchiolitis care 24 . This study found numerous barriers to de‐implementing continuous monitoring, including unclear or absent guidelines for stopping continuous monitoring, clinician knowledge, unit culture, and clinician expertise in bronchiolitis management.…”
Section: Discussionmentioning
confidence: 99%
“…Wolk and colleagues conducted a multicentre qualitative study of clinicians at United States hospitals with low and high continuous pulse oximetry use in bronchiolitis care 24 . This study found numerous barriers to de‐implementing continuous monitoring, including unclear or absent guidelines for stopping continuous monitoring, clinician knowledge, unit culture, and clinician expertise in bronchiolitis management.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcomes were acceptability, appropriateness, and feasibility of the deimplementation strategies. 21 We also measured perceived safety of intermittently spot-checking oxygen saturation instead of using cSp o 2 . To estimate penetration 24 of guideline-concordant care 2 , 3 , 4 of patients with bronchiolitis not receiving supplemental oxygen, we assessed the change in cSp o 2 use between the baseline 10 and intervention periods.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcomes were acceptability, appropriateness, and feasibility of the deimplementation strategies . We also measured perceived safety of intermittently spot-checking oxygen saturation instead of using cSp o 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In this issue, Wolk et al describe barriers and facilitators in deimplementing non-guideline adherent use of continuous pulse oximetry (CPO) in pediatric patients with bronchiolitis not requiring supplemental oxygen. 3 Unnecessary CPO use for these patients is associated with increased hospitalization rates, length of stay, alarm fatigue, and costs, without evidence of improved clinical outcomes. Despite these data, many hospitals participating in the multicenter Eliminating Monitor Overuse study struggled to decrease CPO usage.…”
mentioning
confidence: 99%